EXPERIMENTAL DETERMINATION OF DYNAMIC PARAMETERS OF THE TRACTION DRIVE OF A VEHICLE - Nesterenko, V. I. (Science and Transport Progress, 2005)
In work questions of reduction of dynamic influence of wheel pairs on a way are considered. By the example of calculation of a traction drive of the third class the technique of definition of dynamic parameters is shown.